FEASIBILITY STUDY OF SUSTAINABLE COASTAL PROTECTION USING A COMBINATION OF BAMBOO POLE BREAKWATERS AND GREEN MUSSEL (PERNA VIRIDIS) CULTIVATION - Didin Khoiruddin, Ahmad
One of the problems that is quite severe and threatens the ecosystem in coastal areas is abrasion. This is because abrasion can cause huge losses in the form of damage to existing structures in residential areas. Meanwhile, it costs a lot of money to build a large-scale coastal protection building using concrete. For this reason, an effective and stable coastal protection structure with materials that are easy and cheap is needed. The purpose of this study was to obtain an initial design concept of a pole-type bamboo breakwater that can be used for green mussel (Perna viridis) cultivation; examine the role of environmentally friendly natural coastal protection systems in increasing the economic value and social aspects of coastal communities; and able to apply the initial design of the pole-type bamboo coast guard in the coastal case study area of Bedono Village, Sayung Demak District. The method used in this research is to combine and analyze secondary data to get the desired design. The results showed that the ecological conditions of the waters of Bedono Village, Sayung District, Demak Regency had met the requirements to be used as green mussel cultivation sites. After the cultivation principles are fulfilled, the next step is to develop engineering principles by calculating the structural model with the same approach as the case study in Pekalongan waters, Central Java. Namely using bamboo with a minimum length of 7.5 meters and a depth of 2 meters. After being deemed to fulfill engineering principles, then a financial feasibility analysis is carried out. In terms of financial feasibility, it is also considered quite profitable with an NPV value of green mussel cultivation with the step method of IDR 1,202,383. The Net B/C value for green mussel cultivation using the step-by-step method is 1.20, which means that every expenditure of Rp. 1 will increase benefits by Rp. 1.20 for cultivators using the step-by-step method. Based on the eligibility criteria for NPV and Net B/C, green mussel cultivation using the step method is feasible. The last principle as a complement is the ecological principle, this structural concept is considered to fulfill ecological principles based on a rapid assessment carried out by the author and requires deepening of each component.